“They’re Lacking Purpose. It’s a Recipe for Suicide.”: Masculinity and Gender-Based Inequalities in Deaths of Despair in England - Timothy Price (American Journal of Men's Health)
This qualitative study explores the factors contributing to gender-based inequalities in “deaths of despair” (DoD) – those deaths from suicide, drug overdoses, and alcohol-specific causes – among men in two deindustrialised towns in North East England. Understanding gender-based disparities in these causes of death sheds important light on how social and economic factors intersect with certain facets of masculinity, such as stoicism and self-reliance, to drive vulnerability. Data were collected through semi-structured interviews and one focus group with 54 stakeholders – people whose work is related to DoD, such as mental health treatment and public health practice – and community members in Middlesbrough and South Tyneside, two towns with above average rates of DoD. Participants included both men and women, predominantly of middle-age or older, with most participants unemployed or retired. Data were analysed using Iterative Categorisation, with findings interpreted through thematic analysis. The study generated three key themes: industrial history and masculinity, masculinity and class, and masculinity as a barrier to help-seeking. The findings demonstrate that economic decline following deindustrialisation resulted in distress and created unique risk factors for substance use and self-harm for men. These results suggest that effective interventions to reduce DoD among men in post-industrial settings must avoid pathologising masculinity itself. Instead, strategies should focus on the broader structural forces that undermine men’s access to stable, fulfilling employment and offering forms of support that are compatible with masculine identity. By addressing these determinants, interventions can more effectively close gender-based inequalities and reduce the rate of DoD in deindustrialised areas.